PESAT application Personal Security Administrator Tool / Law Yong Jin - Law , Yong Jin (2004)
The thesis report is written to describe the development of PESAT application in depth. It contains from the project objective, definition, scope from the beginning; extends to literature review, study on existing application, software process model, and application development tool, functional and non-functional requirements and ended with the system structure design, System process design and user-interface design. The report will be furthered with more details on system implementation, testing and evaluation on the coming semester. It is well-structured within layouts and contents to cover as much information as an application development proposal. PESAT is a security and administration application that tends to protect the security of personal computer with the administration of the computer on the same time. PESAT enhances the current existing security and administration tools m the market, by improving the weaknesses and expanding the strengths of those existing application. In short. PESAT is a well-organized, securable, exceptional and superb security administrator tool that is going to be developed It is built using the current application development tools with a resourceful and fundamental research on the security and administration arenas. The high expectation the outcome of PESAT application is to construct an application that approaches the conceptual of computer security as well as administration. In order to step in a successive development of PESAT, it must be well-planned, well-structured and well-organized to meet every functional and non-functional requirement.